SENI SINGIRAN DALAM RITUAL TAHLILAN PADA MASYARAKAT ISLAM TRADISIONAL JAWA - Kusnadi - (Imaji, 2006)
The phenomenon of Singiran in tahlilan is typically Javanese.Singiran is a form of Javanese singing art (tembang) performed in the middle oftahlilan ritual, especially when tahlil words are being recited. The aims of thiswriting are (1) to describe the form of Singiran song found among the society ofNgemplak Nganti, Sendangadi Mlati Sleman, and (2) to describe the function ofSingiran art in the context of Islamic traditional Javanese culture.The form of Singiran song is typically different from other genres ofJavanese songs, such as those in karawitan, pedalangan and santiswara/larasmadya. The laras (pitch) used is both pelog (seven-tone gamelan scale) andslendro five-tone gamelan scale). Laras pelog is played in the opening andclosing songs while laras slendro is for songs in the middle. All the rhythms aremetrical with medium speed and then high speed at the end of the songs. Thisspeed arrangement forms a dramatic pattern of a single cone. The literaryornaments used are purwakanthi guru swara with rhyming scheme of a-a or a-aaThe functions of Singiran in the context of tahlilan ritual are (a) as an Islamicpropagating medium, and (b) as a means of tightening brotherhood among themembers of tahlil groups.Key words: Singiran, tahlilan, Islamic traditional Javanese culture